Cut Throat Injury: One Year Study (Medical Forum Monthly, 2024)
Objective: To evaluate the cause and pattern of cut throat injury.Study Design: Prospective studyPlace and Duration of Study: This study was conducted in Abbasi Shaheed Hospital and Karachi Medical and Dental College from 01.09.2012 to 31.08.2013.Materials and Methods: Total number of patients with cut throat were 42 patients, in which 33 were selected in this study. During this period, those patients who came in emergency room in Abbasi Shaheed Hospital with cut throat injury were included in this study.Results: In this study male were 24 patients (72.72%) and female were 9 (27.27%). Male female ratio was 2.66:1. Maximum incidence of age was between 21-30-years 9 cases (27.27%). Accidental cause was the main cause of cut throat with 19 patients 57.57%. In 9 (27.27%) cases of suicidal, 7 (77.77%) patients was history of psychiatric illness. Zone II was the commonest site which was 20 cases (60.60%) Skin and soft tissue is the commonest structure involved which was 20 cases (60.60%). 26 patients (78.78%) were discharge from ward after treatment.Conclusion: Proper assessment the cause and accurate treatment may prevent complication